The Method of snakes and ladders game in increasing student’s knowledge and attitude about prevention of pes disease - Muhammad Zamzami; Dwi Astuti; Kusuma Estu Werdani (Faculty of Public Health, Andalas University, 2016)
SubdistrictBoyolaliSelois a pest endemic area, tillat any timecould bean epidemicof pest diseaseanymorebecausediscoveryis stillpositivetitersin miceandhumanbloodspecimens. Preventionneeds to bedonerightthrough thechild’searlyelementary studentstoimprove their knowledge andattitudes. The aims this research is for knowing there are the influence of health education using ladder snake method about prevention of pest disease towards knowledge level and ttitude of students in elementary school of 1 Selo Boyolali. This research method are Quasi Eksperiment with design Non-Equivalent Control Group. Research subjects areelementary school studentsgrades 4-6are divided intoan experimental groupanda control groupusing70samples. Statistical test with significant level (α=0,05) using Paired sample t-test, showed there is difference average value on knowledge level(p-value=0.000) andattitude(p-value=0.000) in the experimental groupaftertreatment and there is no difference average value on knowledge(p-value=0.202) andattitude(p-value=0.750) in the control group. The result of Independent t-test showed there any effect of health education with ladder snake about prevention of pest disease on knowledge level (p-value=0,000) and attitude (p-value=0,000). Suggestedto health practitionersto disseminate society how to prevention pest disease, especially about vector and reservoir pest disease